2012
DOI: 10.4314/ajcem.v13i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies on Proteeae Isolates from Clinical Specimens in the Laquintinie Hospital in Douala, Cameroon

Abstract: The tribe Proteeae is a group of bacteria within the family Enterobacteriaceae and is responsible for most cases of nosocomial infections in hospital settings. The objective of this study was to determine the prevalence of members of Proteeae from clinical specimens in Laquintinie hospital in Douala. Specimens were collected from patients and screened for Proteeae using standard microbiological and biochemical methods (API 20 Enterobacteriaceae gallery).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…[ 12 ] However, some studies have reported a lower prevalence of 1.1%[ 13 ] and 3%[ 14 ] while other studies have shown a higher prevalence ranging from 14.4% to 28.7%. [ 15 16 17 ] In our study, the highest percentage of Proteus species was isolated from pus specimens (80.2%) followed by urine (8.9%). Similar observation has been reported by other studies whereas some studies have reported isolates more commonly from urine than other clinical specimens.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…[ 12 ] However, some studies have reported a lower prevalence of 1.1%[ 13 ] and 3%[ 14 ] while other studies have shown a higher prevalence ranging from 14.4% to 28.7%. [ 15 16 17 ] In our study, the highest percentage of Proteus species was isolated from pus specimens (80.2%) followed by urine (8.9%). Similar observation has been reported by other studies whereas some studies have reported isolates more commonly from urine than other clinical specimens.…”
Section: Discussionmentioning
confidence: 63%
“…P. mirabilis was the most common (62.4%) among all the isolates which is similar to the findings of other studies. [ 11 13 15 19 ] P. mirabilis was isolated in highest number from urine as it has a higher propensity for colonizing the urinary tract due to difference in its pathogenicity. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were motile, methyl red, and gelatin liquefication positive for urease, catalase, citrate, urease, and gelatin. The isolates could sour glucose on Kliger iron agar, resulting in (Alkaline) red color on the slant and lower (acidic) yellow color with gas and H2S production 16 ; oxidase, indole, and vogues-Proskauer were all negative 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…Providencia species occur in normal feces and have been isolated from epidemic and sporadic causes of diarrhea, though their importance in the causation of diarrheal disease is not easy to assess. 53 Pseudomonas aeruginosa can colonize (0%-10%) the intestine of the newborn during the first days of life. 54 Clinically, the infection may be asymptomatic at first, later developing into grayish-blue stool color or watery diarrhea, profuse vomiting, and systemic symptoms.…”
Section: Introduction and Epidemiologymentioning
confidence: 99%